Sexual orientation, crime victimization, and relationship to the offender: Insights from New Zealand police records, 2014–2024 - Gilmour, A.L.; Feinstein, B.A.; Plum, A. (Public health (London), 2026)
To examine sexual orientation differences in crime victimization rates by strangers and known offenders in a nationally representative sample of 2.58 million cisgender New Zealand (N.Z.) residents. We linked N.Z. Census data and police records from 2014 to 2024 to examine sexual orientation differences in rates of crime victimization (any crime, sexual assault, crime with a weapon, violence, and serious violence) separately for cisgender men and women. We further examined rates of each crime offence by strangers versus known offenders by sexual orientation, stratified by gender. We used logistic regression stratified by gender, adjusting for demographic covariates. Sexual minority (SM) individuals faced higher victimization risk across categories of crime compared to heterosexual people, with the most consistent heightened risk observed for sexual assault. Bisexual people experienced heightened risk of victimization from both strangers and known offenders, whereas homosexual men generally experienced heightened risk of victimization from known offenders and homosexual women from strangers. There are differences in risk of being offended by strangers and known individuals by sexual orientation, with particularly stark disparities observed for women and bisexual individuals. Policymakers and social service organizations should consider the unique vulnerabilities of subsets of SM individuals when implementing crime prevention strategies.